A Primary Cerebellar Glioblastoma Multiforme Mimicking Vestibular Schwannoma. Issue 7 (October 2016) - Gao, Shuxia; Liu, Xiaogang; Cheng, Pengfei; Yuan, Xunhui; Niu, Jianyi; Bai, Yun'an; Xi, Bin
Abstract : Abstract: Cerebellar glioblastoma multiforme (cGBM) is rare in adults, accounting for <1% of all patients with glioblastoma multiforme (GBM). The accurate diagnosis of cGBM is important for establishing a suitable therapeutic schedule. However, the diagnosis of cerebellar GBM is not usually suspected preoperatively because of its rarity. Generally, patients with cGBMs typically presented with symptoms of raised intracranial pressure, and infrequently cerebellar symptoms such as gait ataxia and disequilibrium. Nevertheless, the authors reported a cGMB patient, with his clinical presentations and imaging characteristics mimicking a vestibular schwannoma. To the best of our knowledge, this is the first reported patient with cGBM mimicking a vestibular schwannoma. Furthermore, the diagnosis, treatment, and prognosis for cGBM were broadly investigated.